The Relationship between Postpartum Mother's Education and Postpartum Mother's Knowledge of Mastitis in the Independent Midwife Practice of Romauli Medan Marelan 2021 - Ermawaty Arisandi; Merlina Sinabariba; Meriati Bunga Arta Purba; Angelin Selly Maduwu (Science Midwifery, 2021)
Mastitis is a problem in the breast that is characterized by pain caused by inflammation of the breast which can be accompanied by infection or non-infection. Mother's lack of knowledge about the breastfeeding process can cause errors in breastfeeding positions which result in blisters on the mother's nipples. In addition, it also causes the process of releasing and releasing breast milk that is less than optimal, causing breast engorgement. This study aims to determine the relationship between postpartum mother's education and knowledge about Mastitis in the Romauli Independent Midwife Practice in 2021. This study used a descriptive correlation method. The sample in this study was postpartum mothers 0-42 days in labor and postpartum visits at the Romauli Independent Midwife Practice in 2021 with a total of 30 respondents. Researchers used primary data and the data were processed using SPSS and presented using open tables. The relationship between postpartum mother's education and knowledge about mastitis at the Romauli Independent Midwife Practice in 2021 based on the results of the Spearman's-rank test, p-value = 0.009 (p<0.05) which means that there is a relationship between postpartum mother's education and knowledge of mastitis with sufficient strength of the relationship. Knowledge of postpartum mothers about mastitis can be influenced by important factors, one of which is education. The higher a person's education, the better his knowledge will be.